Prevalence of estrogen receptor alpha PvuII (c454-397T>C) and XbaI (c454A>G) polymorphisms in a population of Brazilian women - Araújo,Karine Lourenzone (2011)
The aim of this work was to study the estrogen receptor alpha (ERS1) PvuII and XbaI gene polymorphisms prevalence in randomly selected women population from Rio de Janeiro and Espírito Santo states in Brazil by polymerase chain reaction restriction fragment lengths polymorphism (PCR_RFLP) methodology. It was shown that Rio de Janeiro women exhibited a significantly different prevalence of XbaI polymorphism comparing to Espirito Santo women. Nonetheless, similar prevalence of PvuII polymorphism was found in both women´s populations. Moreover, a strong linkage disequilibrium was observed between these SNPs reinforcing the hypothesis of differential pattern of inheritance observed on such populations.